2024
DOI: 10.1021/acs.inorgchem.3c04246
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Reduction by an Iron(I) Porphyrinate System: Effect of Hydrogen Bonding on the Second Coordination Sphere

Chengxu Zhu,
Carmine D’Agostino,
Sam P. de Visser

Abstract: Transforming CO 2 into valuable materials is an important reaction in catalysis, especially because CO 2 concentrations in the atmosphere have been growing steadily due to extensive fossil fuel usage. From an environmental perspective, reduction of CO 2 to valuable materials should be catalyzed by an environmentally benign catalyst and avoid the use of heavy transition-metal ions. In this work, we present a computational study into a novel iron(I) porphyrin catalyst for CO 2 reduction, namely, with a tetraphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Several studies have reported that the presence of groups able to provide hydrogen-bonding interactions is beneficial for electroreduction processes, since it facilitates easy proton transfer and stabilize key intermediates. 77–82…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that the presence of groups able to provide hydrogen-bonding interactions is beneficial for electroreduction processes, since it facilitates easy proton transfer and stabilize key intermediates. 77–82…”
Section: Resultsmentioning
confidence: 99%